Epidermal growth factor receptor and Kras gene expression: Reliability of mutational analysis on cytological samples. Issue 7 (26th July 2012) - Bozzetti, Cecilia; Negri, Francesca V.; Azzoni, Cinzia; Naldi, Nadia; Nizzoli, Rita; Bortesi, Beatrice; Zobbi, Valentina; Bottarelli, Lorena; Tiseo, Marcello; Silini, Enrico Maria; Ardizzoni, Andrea
Abstract Epidermal growth factor receptor (EGFR) and Kras gene mutations are crucial for discriminating patients responsive to anti‐EGFR drugs in non‐small cell lung cancer (NSCLC) and colorectal cancer (CRC), respectively. The majority of NSCLCs come to clinical attention at an advanced stage when surgery is no longer recommended and a considerable number of them are diagnosed by cytology only. A large number of metastatic CRCs are also diagnosed by imaging and minimally invasive techniques such as fine‐needle aspiration biopsy. Here, we report our experience in the mutation analysis of EGFR and Kras on cytological material obtained from superficial and deep lesions of NSCLC and CRC. Our series included 63 cytological specimens from primary or metastatic lesions of 42 NSCLCs and 21 CRCs. The cytological material was adequate for the mutation analysis in 39/42 (93%) NSCLCs and in 20/21(95%) CRCs. EGFR and Kras mutations were found in 9 (23%) and 9 (23%) NSCLC cases, respectively. Kras mutations were found in 9/20 (45%) CRC specimens. Histological samples from the primary tumors were available in 9/42 NSCLCs and in 17/21 CRCs. The agreement of EGFR and Kras mutational status in cytological vs. histological samples was 100% for NSCLC and 88% for CRC. Our results suggest that standard cytology provides adequate material for the assessment of EGFR and Kras mutational status in NSCLC and CRC patients and could be specifically indicated in patients not eligible for surgery but candidate to anti‐EGFR therapy. Diagn. Cytopathol. 2013. © 2012 Wiley Periodicals, Inc.